2005
DOI: 10.1089/bsp.2005.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in Crisis? Understanding Trust in Government and Public Attitudes Toward Mandatory State Health Powers

Abstract: In response to the possibility of a bioterror attack using smallpox, many states have updated and revised their current public health laws in line with the Model Act, which would effectively give states the right to invoke mandatory state health powers, such as quarantine or vaccine. Previous studies have supported the importance of allying with the public in creating and implementing effective bioterror response policies. Historical case studies and recent research suggest that when the public is not supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 17 publications
(16 reference statements)
0
40
1
Order By: Relevance
“…These findings are compatible with previous research that has shown fairness beliefs and trust to be especially important to individual decision making and interpretation of events under conditions of uncertainty. 74,75 The significant association between values or preexisting risk beliefs and reactions to uncertainty messages in this research is noteworthy given that the 2 samples reflected different cultural and ethnic backgrounds, social histories, and geographic locations. Moreover, participants responded to actual past messages from leaders and public health officials that had been constructed based on in-place risk/crisis communication plans thought to reflect best practices at the time of the 2001 anthrax episode.…”
Section: Standardized Bsmentioning
confidence: 83%
See 2 more Smart Citations
“…These findings are compatible with previous research that has shown fairness beliefs and trust to be especially important to individual decision making and interpretation of events under conditions of uncertainty. 74,75 The significant association between values or preexisting risk beliefs and reactions to uncertainty messages in this research is noteworthy given that the 2 samples reflected different cultural and ethnic backgrounds, social histories, and geographic locations. Moreover, participants responded to actual past messages from leaders and public health officials that had been constructed based on in-place risk/crisis communication plans thought to reflect best practices at the time of the 2001 anthrax episode.…”
Section: Standardized Bsmentioning
confidence: 83%
“…[38][39][40] As a significant act unfolds, some ongoing uncertainties would have been predicted; others will become apparent only as the event develops. [6][7][8][9]58,59,70,87 Distrust of government actions and decisions will be high in some communities, moderate in others, 11,17,23,28,75 and preexisting social and environmental vulnerabilities to extreme events will contribute to an unequal potential for loss. 6,50,89 During this dynamic phase, skilled communications about decontamination strategies, protection of public health, cleanup, restoration, and reoccupancy will be essential to support efforts to protect public health and maintain/restore public confidence within a context of disturbing events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For public administration specifically, trust affects programmatic performance because it is associated with the delegation of administrative authority (Marlowe 2004;Metlay 1999), excessive oversight and an over-reliance on formal rules and procedures (Ruscio 1996), and public cooperation and compliance with laws and regulations (Marien and Hooghe 2011;Scholz and Lubell 1998;Taylor-Clark, Blendon, Zaslavsky, and Benson 2005). The link between low trust, excessive micromanagement, and reduced performance is at the base of past bureaucratic reform efforts, such as the Winter Commission (National Commission on the State and Local Public Service 1993) and the National Partnership for Reinventing Government (National Performance Review 1993).…”
Section: "Trust Has Been Linked With Adherence To Public Health Guidementioning
confidence: 99%
“…For example, trust has been linked with adherence to public health guidelines, such as participation in vaccination programs (Larson and Heymann 2010;Quinn et al 2009;Sankar, Schairer, and Coffin 2003) and compliance with evacuation orders during natural disasters (Feldheim and Wang 2003-4;Taylor-Clark et al 2005). Lack of trust in regulatory agencies charged with the disposal of radioactive waste is the most significant obstacle that a successful radioactive waste management policy must overcome (Clark County 2003;Office of Technology Assessment 1982).…”
Section: "Trust Has Been Linked With Adherence To Public Health Guidementioning
confidence: 99%